Self-Control and Grit in Thesis Achievement among Final-Year Students: A Study at the Faculty of Da’wah and Communication, State Islamic University of North Sumatra - Aini, Fadhilatul; Metia, Cut (TEMALI : Jurnal Pembangunan Sosial, 2024)
This study aims to determine the role of self-control and grit among final-year students at the Faculty of Da’wah and Communication, State Islamic University of North Sumatra. The research employs a quantitative approach with a sample of 100 final-year students who are working on their theses or journal articles. Data collection involved the use of two scales: a self-control scale encompassing behavioral control, cognitive control, and decision-making control and a grit scale covering aspects of interest consistency and perseverance. We performed data analysis using simple regression. The findings reveal that self-control significantly and positively affects grit, with a significance value ranging from 0.01 to 0.05. Self-control contributes 11.2% to grit, indicating that the ability to control oneself influences the level of perseverance and consistency among students. The main contribution of this study is to provide insights into how self-control can enhance grit in final-year students, supporting them in achieving academic goals more consistently and diligently.